Update-ordering for database consistency in distributed database environments - Wan Nor Shuhadah Wan Nik (Fakulti Sains dan Teknologi, 2011)
Database consistency is one of the major issues in replicated and distributed database environment. Data replications in distributed systems have been studied extensively for many years. It is quickly becoming a critical tool for providing high availability, survivability and high performance for replicated database. However, to provide useful replication one has to solve the non-trivial problem of maintaining data consistency between all replicas. The existing replication control mechanism can be categorized into two spectrums: the logical design for the replicated nodes and its transaction management mechanism. These two spectrums give a major impact to the performance and the consistency of replicated database.